Implementasi Metode Objective Matrix (OMAX) Untuk Pengukuran Produktivitas Pada PT.ABC - Hana Catur Wahyuni; Setiawan Setiawan (Universitas Muhammadiyah Sidoarjo, 2017)
Productivity is an indicator of a company's development. Therefore, every company must perform the measurement of productivity in one cycle consisting of: productivity measurement, productivity evaluation, planning productivity and productivity improvement. PT ABC is a company engaged in export-oriented shoe industry. The purpose of this study was to determine the level of productivity in PT ABC for injection area so that corrective measures can be formulated. Productivity measurement method used is the objective matrix (OMAX). The measurement results showed that the total value of productivity in the area of injection machine is 355.